EFEKTIVITAS PENERAPAN APLIKASI SISKEUDES SEBAGAI SISTEM PENGAWASAN PENGELOLAAN KEUANGAN DESA (STUDI KOMPARATIF DI KOTA AMBON DAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT) - Linda Grace Loupatty (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is a comparative study that aims to evaluate whether the application of the Village Financial System (Siskeudes) application and the Village Financial Management Oversight System in Ambon City and Kairatu District, West Seram Regency has been running effectively. The conceptual framework in this study uses the effectiveness theory of Walter Jack Duncan (1981) using indicators of goal attainment, integration and adaptability. The types of data used are primary data and secondary data. Data collection techniques are observation, interviews and documentation. The results of the study show that the implementation of Siskeudes in 30 villages/countries in Ambon City has been running effectively. Around 25 Villages/Countries namely Leahari Country, Hutumuri Country, Rutong Country, Refinery Country, Hatalai Country, Ema Country, Hukurila Country, Naku Country, Latuhalat Country, Nusaniwe Country, Seilale Country, Urimesseng Country, Batu Merah Country, Soya Country, Villages Latta, Nania Village, Waiheru Village, Negeri Halong, Negeri Hatiwe besar, Negeri Laha, Negeri Rumahtiga, Negeri Tawiri, Hunuth Village, Poka Village, Wayame Village have implemented village financial management procedures in a transparent, accountable, participatory, orderly and disciplined budget. And 5 other villages, namely Negeri Amahusu, Negeri Passo, Negeri Hative Kecil, Galala Village and Negeri Lama Village, are still in the process of improving their financial management to make it better. The monitoring system has also been running effectively so that the implementation of Siskeudes in 30 villages/countries in Ambon City has had a very positive impact, which has been able to improve village financial management performance. However, the results of research in 6 villages in Kairatu District, West Seram Regency, namely in Kamarian Village, Seruawan Village, Uraur Village, Waipirit Village and Hatusua Village, show that the implementation of the siskeudes application and the village financial management monitoring system has not been effective. This is because the implementation of the siskeudes application is still offline. Financial reporting that is still offline creates many problems. Resulting in village government apparatus losing authority in the village financial management process to become more transparent, accountable and participatory, as well as more orderly and budget discipline. In addition to the offline application of the Siskeudes application, several factors were found which were considered to be obstacles in achieving goals, integration and adaptation of the Siskeudes application in Kairatu District, West Seram Regency, namely; The quality of human resources, both village apparatus and village financial operators, is still inadequate, IT mastery is low, the submitting or posting process is only under the authority of district-level operators, the available Internet network is inadequate, so the system often experiences errors, not all types of activities are contained in the Siskeudes application, the needs of each village are not the same so that Siskeudes must be adapted to the needs of the village, the availability of IT infrastructure facilities in the village is inadequate, lack of training, technical guidance and assistance, regulations that change frequently and minimal operational budgets.